1983
DOI: 10.1063/1.332716
|View full text |Cite
|
Sign up to set email alerts
|

TeOx thin films for an optical disc memory

Abstract: Tellurium suboxide thin films TeOx were found to change in refractive index and extinction coefficient on thermal or optical heating, with accompanying changes in the reflectivity and transmission. The preparation method and thermal or optical properties of the TeOx thin films were investigated to obtain a stable and highly sensitive optical disc memory. A two-source evaporation method using Te and TeO2 provided uniform and any desired composition. The properties of the film depended on the x value; increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…The presence of metallic Te in tellurium oxide films has been the subject of a number of investigations, which have confirmed the ability of this material to exhibit appropriate changes in its optical properties following thermal treatment [1][2][3][4]8]. These changes have been attributed to the observed crystallization of Te micrograins in the films upon thermal treatment [2]. Overall, XRD studies on heat-treated tellurium oxide films [18] have revealed that the films are initially amorphous prior to heat treatment, followed by the formation of crystalline Te metal with subsequent crystallization of TeO 2 at higher temperatures.…”
Section: Us (O1) Us (O2) Us (Wo)mentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of metallic Te in tellurium oxide films has been the subject of a number of investigations, which have confirmed the ability of this material to exhibit appropriate changes in its optical properties following thermal treatment [1][2][3][4]8]. These changes have been attributed to the observed crystallization of Te micrograins in the films upon thermal treatment [2]. Overall, XRD studies on heat-treated tellurium oxide films [18] have revealed that the films are initially amorphous prior to heat treatment, followed by the formation of crystalline Te metal with subsequent crystallization of TeO 2 at higher temperatures.…”
Section: Us (O1) Us (O2) Us (Wo)mentioning
confidence: 99%
“…for photon energies below the band gap. In earlier studies [2,3] on TeO x films with x less than 1.1, the XPS revealed two well-separated peaks (Te 3d 5/2 ) of nearly the same amplitude, attributable to Te metal (∼573 eV) and Te in TeO 2 (∼576 eV), respectively. However, in the present work, the Te 3d 5/2 spectrum (figure 8) looks like a single peak centred at about 576 eV.…”
Section: Us(wo)a Us(o)a Hs(wo) Hs(wo)a Hs(o) and Hs(o)a Types Asmentioning
confidence: 99%
See 1 more Smart Citation
“…The as-deposited TeO x film in vacuum actually consists of Te metal micrograins usually with diameters that are less than 2 nm and embedded in an amorphous TeO 2 matrix of a special granular structure [20][21][22][23]. The recording mechanism has been explained by two theories: one is the phase transformation of Te grains from amorphous to crystalline [24][25][26][27], and the other is the segregation of Te particles to the near surface [20,21]. Regardless of the actual reasons behind the change in optical behaviors of the TeO x film, the result indicates a visible change from bright to dark under laser pulse irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurium dioxide (TeO 2 ) is an important material in both amorphous as well as crystalline form and finds application in active optical devices in particular, a huge hyper-susceptibility, deflectors, modulators, c-ray detectors, and gas sensors because of its high acousto-optic figure of merit, chemical stability, and mechanical durability [1][2][3][4][5][6]. It is also not hygroscopic and has superior physical properties such as high dielectric constant and low melting point (800°C) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%